Deradicalization of Religion Through Aswaja Course at Lamongan Islamic University - PS , Alaika M Bagus Kurnia; Ridho , Muh. Makhrus Ali; Bachri , Affan (LPPPM STAI Darul Hikmah Bangkalan, 2022)
One of the phenomena that occur in this contemporary era is that the teachings of radicalism are increasingly rising amid the dynamics of people's lives. Some even think that cases of radicalism in Indonesia are getting chronic and have entered the red category or are very dangerous. It is very important to act to deradicalize, the deradicalization process needs a Religion and Ideology approach. Lamongan Islamic University strives to take preventive steps or can be called anticipating and breaking deviant religious understandings (radical understanding). Among these preventive steps are having a vision and mission of having faith and practicing the treatise of Islamiyah Ahlussunnah wal Jama'ah an-Nahdliyah and requiring all students to take Aswaja courses. Some of the main steps are making the Aswaja course a radical bulwark, understanding more deeply the basics of Aswaja amaliyah and practicing it consistently, conveying the main Aswaja which is a firqoh or group of survivors (al-Firqah al-Najiyah), paying attention to the continuation of the scientific sanad that Aswaja has until Rasulullah Muhammad SAW, then students are equipped with Aswaja values, namely tawassuth (moderate), tasamuh (tolerant), tawazun (balanced) and I’tidal (fair).